IMPLEMENTATION OF TRAFFIC RULES FOR PEDESTRIANS IN BANDAR LAMPUNG CITY: IMPLEMENTASI TENTANG TATA CARA BERLALU LINTAS BAGI PEJALAN KAKI DI KOTA BANDAR LAMPUNG - Rizki, Bawoni; Nurhayati, Agustina; Gumiri, Erik Rahman (Constitutional Law Society, 2025)
This study analyzes the implementation of pedestrian traffic rules in Bandar Lampung City as regulated in Article 63 paragraph (1) of Local Regulation No. 10/2017 concerning Transportation. The focus lies on the use of pelican crossings, a pedestrian facility with traffic lights designed to enhance safety and comfort. However, public unfamiliarity and limited enforcement have hindered its effectiveness. Using the perspective of Fiqh Siyasah Tanfidziyyah, this research examines how local government policies align with the principle of public benefit (maslahah ‘ammah), deliberation (shura), and obedience to authority (ulil amri). A qualitative field research design was applied, involving observations, interviews with the Department of Transportation officials and pedestrians, and document analysis. The findings reveal that although pelican crossings were initially installed, their operation and socialization have been inadequate, leading to low public awareness and poor compliance. The analysis shows that the lack of government efforts in education and enforcement contributes to the ineffective implementation of the regulation. This study contributes by linking legal implementation with Islamic political jurisprudence, offering insights into the integration of sharia principles in local governance. Practically, the research recommends enhanced socialization, accessible facility design, and inter-agency coordination to improve pedestrian safety.